Digital cash waqf in Indonesia: Opportunities and challenges a systematic literature review with PRISMA framework - Rifaldi Nurul Akbar; Muhammad Iman Kurniawan; Miftah Hur Rahman ZH (Institute of Accounting Research and Novation (IARN), 2025)
This study analyzes the development of digital cash waqf in Indonesia by exploring its opportunities, challenges, and strategic implications. It aims to provide a comprehensive synthesis of the impact of digital platforms on public participation, the efficiency of institutional coordination, and the potential for financial innovations such as Cash Waqf Linked Sukuk (CWLS). Employing a Systematic Literature Review (SLR) guided by the PRISMA framework, the research conducted a rigorous identification and screening process of 195 articles from the Scopus database, ultimately selecting 25 high-quality articles for detailed thematic analysis. The key findings reveal that digital platforms significantly increase participation, particularly among younger generations, driven by ease of use, social influence, and digital literacy. However, the study also identifies complex challenges, including weak coordination among the Indonesian Waqf Board (BWI), nadzir (waqf managers), and Islamic financial institutions, coupled with low public literacy and trust. While innovations like CWLS offer considerable potential for sustainable development, their implementation faces obstacles stemming from an immature regulatory framework and ineffective marketing strategies. Based on these findings, the study concludes that optimizing digital cash waqf requires strengthening regulations, enhancing literacy through digital campaigns, building the capacity of nadzir, and fostering more synergistic institutional collaboration. Future research should explore innovative business models, assess the specific effectiveness of fintech platforms, and investigate the determinants of CWLS adoption from both customer and regulatory perspectives to enrich waqf development strategies in the digital era.